2012
DOI: 10.1016/j.trsl.2012.03.005
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and immunologic features of pulmonary fibrosis in sarcoidosis

Abstract: Sarcoidosis is a multisystem, granulomatous disease that most often affects the lungs. The clinical course is highly variable; many patients undergo spontaneous remission, but up to a third of patients progresses to a chronic disease course. The development of pulmonary fibrosis (PF) in a subset of patients with chronic disease has a negative impact on morbidity and mortality. While sarcoidosis-associated PF can be progressive, it is often referred to as “burnt out” disease, a designation reflecting inactive g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 86 publications
(109 reference statements)
2
32
1
2
Order By: Relevance
“…In our study, booster challenge with PA induced activation of the Th1 immune response including expression of IFN-γ and TNF-α, which may have induced fibrosis and also activation of TGF-β1. BALF lymphocytes and ACE expression are both important in clinical assessments of sarcoidosis [5, 27]. In the present study, the number of inflammatory cells, especially lymphocytes, in the BALF increased from days 21 to 70.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…In our study, booster challenge with PA induced activation of the Th1 immune response including expression of IFN-γ and TNF-α, which may have induced fibrosis and also activation of TGF-β1. BALF lymphocytes and ACE expression are both important in clinical assessments of sarcoidosis [5, 27]. In the present study, the number of inflammatory cells, especially lymphocytes, in the BALF increased from days 21 to 70.…”
Section: Discussionsupporting
confidence: 56%
“…It remains unclear whether or not progressive fibrosis results from persistent granulomatous inflammation [27]. In the sarcoid-remission group of the present study, no lung fibrosis was observed after the initial PA challenge.…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, questions remain whether the process is early or late stage. [28**] Research is necessary to determine whether and when immunosuppression may alter the clinical course. Generally, it is recommended that if accompanying granulomatous inflammation is suspected, immunosuppression should be initiated to prevent further organ damage.…”
Section: Morbiditymentioning
confidence: 99%
“…Generally, it is recommended that if accompanying granulomatous inflammation is suspected, immunosuppression should be initiated to prevent further organ damage. [28**]…”
Section: Morbiditymentioning
confidence: 99%
“…Compared to patients with IPF, pulmonary fibrosis in sarcoidosis is characterised by a chronic course, often involving the upper lobe, and is predominantly of the nonhoneycombing type. Conversely, IPF progresses quickly, is mostly located peripherally or in the lower lobe, with a predominance of honeycombing [15]. This might lead to increased traction on the PA in IPF.…”
mentioning
confidence: 99%